Intangible heritage in Astana Gunungjati Tomb Complex, Cirebon - Ina Helena Agustina; Hilwati Hindersah; Ivan Chofyan; Kintan Ayu Sevila; Chairunisa Matondang (Regional Development Information Center, Universitas Sebelas Maret, 2024)
Astana Gunungjati is a tomb complex for the descendants of the palaces in Cirebon. One of them is the tomb of Sunan Gunungjati, one of The Walisanga and also the King of the Cirebon Sultanate. The purpose of this research was to describe the phenomenon of intangible heritage cultural values from Jeneng-Bekel-Kemit in Astana Gunungjati. Jeneng-Bekel-Kemit is the term used for the caretaker of the tomb. The existence of a caretaker known as kuncen in the Astana Gunungjati room played an important role in the service of tomb pilgrimage tourists. Kuncen at Astana Gunungjati has a unique value system in his work, and values are part of a culture that is an intangible heritage. The research method used a qualitative descriptive method. The method of data collection was carried out by interviewing several kuncen who were met by using Snowball. Field observations were carried out to visually record the space and the activities of the kuncen. The analysis method was carried out using qualitative description. Data was collected and classified. Observations made to the linkage among groups of categories to form a concept. The results of the research show ethical, spiritual, cultural, and esoteric values. The findings can be documented as intangible text attached to the Astana Gunungjati space.